2022
DOI: 10.1021/acsnano.1c07769
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibril Alignment during Assembly Revealed by an X-ray Scattering-Based Digital Twin

Abstract: The nanostructure, primarily particle orientation, controls mechanical and functional (e.g., mouthfeel, cell compatibility, optical, morphing) properties when macroscopic materials are assembled from nanofibrils. Understanding and controlling the nanostructure is therefore an important key for the continued development of nanotechnology. We merge recent developments in the assembly of biological nanofibrils, X-ray diffraction orientation measurements, and computational fluid dynamics of complex flows. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…It is noteworthy to mention that the fibers spun from curved PNFs at the higher Q3 sheath rate (33.9 mL/h) have lower modulus but are more extensible than the fibers assembled at a Q3 rate of 24.9 mL/h (Figure a). This is in opposition to previous observations of fiber assembly from cellulose nanofibrils or straight PNFs, as increased sheath flow rate results in higher acceleration of the core and typically results in a higher degree of fibril alignment and a higher fiber modulus. ,,, To further address this contradiction, in situ small-angle X-ray scattering (SAXS) measurements of the curved fibril alignment in the channel, under different flow conditions, were employed. Due to the low signal/noise ratio downstream of the second sheath flow (Q3), reliable data on the effect of the Q3 flow rate could not be obtained.…”
Section: Resultsmentioning
confidence: 75%
“…It is noteworthy to mention that the fibers spun from curved PNFs at the higher Q3 sheath rate (33.9 mL/h) have lower modulus but are more extensible than the fibers assembled at a Q3 rate of 24.9 mL/h (Figure a). This is in opposition to previous observations of fiber assembly from cellulose nanofibrils or straight PNFs, as increased sheath flow rate results in higher acceleration of the core and typically results in a higher degree of fibril alignment and a higher fiber modulus. ,,, To further address this contradiction, in situ small-angle X-ray scattering (SAXS) measurements of the curved fibril alignment in the channel, under different flow conditions, were employed. Due to the low signal/noise ratio downstream of the second sheath flow (Q3), reliable data on the effect of the Q3 flow rate could not be obtained.…”
Section: Resultsmentioning
confidence: 75%
“…During this process, shear and extensional flows aligned the CNFs and induced the ionic bonding of the CNFs. 17 Our findings demonstrate that modifying the surface activity of cellulose molecules could give rise to materials with enhanced crystallinity and, hence, thermal conductivity. The results collectively indicate that nanocellulose is a highly attractive material for thermal management applications.…”
mentioning
confidence: 63%
“…We found that filaments with high thermal conductivity had high crystallinity, resulting from the alignment and ion-induced gelation of CNFs during the flow-focusing process. During this process, shear and extensional flows aligned the CNFs and induced the ionic bonding of the CNFs . Our findings demonstrate that modifying the surface activity of cellulose molecules could give rise to materials with enhanced crystallinity and, hence, thermal conductivity.…”
mentioning
confidence: 72%
“…We depicted in detail the multiple merits of these biomimetic nanomaterials, including immune evasion, prolongation of the circulation time, enhanced biocompatibility, and wonderful tumour-targeting and tumour-selecting efficacy. In light of these multiple merits, the biomimetic nanomaterials exerted superior effects on alleviating the hypoxic TME and improving tumour treatment outputs relative to other materials ( Li et al, 2021b ; Gowda et al, 2022 ; Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%